Acute Effects of Ammonia Nitrogen or Nitrite Nitrogen Exposure on Micropterus salmoides and the Post‐Exposure Recovery - Zeguo Zeng; Shuifa Zhu; Fan Zhou; Jie Chen; Xiaoming Shen; Wei Liu; Xiaofeng Zhang; Gaohua Yao (Aquaculture, Fish and Fisheries, 2025)
ABSTRACT To provide guidance for the actual cultivation of Micropterus salmoides, the effects of ammonia‐nitrogen (ammonia‐N) or nitrite nitrogen (nitrite‐N) stress on enzymatic activity, tissue structure and gut microbiota were investigated. The experimental groups consisted of Group 1 (control group), Group 2 (ammonia‐N stress group), Group 3 (ammonia‐N stress recovery group), Group 4 (nitrite‐N stress group) and Group 5 (nitrite‐N stress recovery group). In these groups, the LC50 of ammonia‐N and nitrite‐N were measured over 96 h. The superoxide dismutase (SOD), acid phosphatase (ACP) and alkaline phosphatase (AKP) activities in the experimental groups showed a trend of first increasing and then decreasing. The SOD activity of Groups 1, 3 and 5 was significantly higher than that of Group 2 at 192 h, whereas the malondialdehyde (MDA) index was significantly lower than that of Groups 2 and 4. The ACP and AKP activities of Groups 1, 3 and 5 were significantly higher than those of Groups 2 and 4 at 192 h. Histology observation revealed the liver cells gradually worsened with increasing duration of stress; Groups 3 and 5 were less severe than Groups 2 and 4. The gills were similar to those of the liver. After ammonia‐N stress, Proteobacteria, Actinobacteria and Candidatus Bacilloplasma decreased, whereas Fusobacteriota, Mycoplasma and Cetobacterium increased. After nitrite‐N stress, Firmicutes, Actinobacteria and Candidatus Bacilloplasma decreased, whereas Fusobacteriota, Aeromonas, Cetobacterium and Mycoplasma increased. During recovery period, Fusobacteriota, Cetobacterium and Mycoplasma continued to increase. The microbial diversity of Groups 3 and 5 was higher than that of Groups 2 and 4. In conclusion, 50 mg/L ammonia‐N or 45 mg/L nitrite‐N caused changes in enzyme activity, damage to the liver and gills and alterations in the gut microbiota. Besides, the physiological condition of M. salmoides did improve after recovery but did not return to the pre‐stress state.